Preliminary geochemical data of the mafic rocks from the Ovacik and Pülümür Ophiolite Zone (Eastern Anatolia, Turkey): implications for the geodynamic evolution of the Northern Neotethyan Ocean - Çimen, Okay; Önal, Ayten Öztüfekçi (Ofioliti, 2018)
The Izmir-Ankara-Erzincan-Sevan-Akera Suture Belt (IAESASB) stretches from the Aegean Sea to the Lesser Caucasus and includes the remnants of the Northern Neotethys. The Ovacık and Pülümür Ophiolite Zone (OPOZ) to the north of Tunceli is less-known members of this belt. In this study, preliminary geochemical data from the basaltic and gabbroic rocks from this zone are presented to provide the first insights into their geochemistry. The studied mafic samples exhibit geochemical characteristics of an intra-oceanic subduction system. Three types of samples were differentiated on the basis of their major, trace and rare earth element (REE) geochemistry. The first one is boninitic and displays highly depleted elemental pattern (relative to N-MORB) and concave REE profile. The second type is akin to back-arc basin basalts (BABB) and generally reflects normal-MORB (NMORB)-like high field strength element (HFSE) patterns coupled with negative Nb anomalies. The last type is relatively similar to the BABB-type, but it lacks the marked negative anomaly in Nb and can be ascribed to the mid-ocean ridge basalt (MORB). The overall geochemical features suggest that these mafic rocks were predominantly generated in a supra-subduction setting from a subduction-modified mantle source. It is further suggested that the Ovacık and Pülümür Ophiolite Zone was formed in an oceanic arc-basin system within the northward subducting Northern Neotethys.